Child Abuse and Neglect: Screening for Risks During the Perinatal Period - Besier, T.; Pillhofer, M.; Botzenhart, S.; Ziegenhain, U.; Kindler, H.; Spangler, G.; Bovenschen, I.; Gabler, S.; Künster, A. K. (Geburtshilfe und Frauenheilkunde, 2012)
Purpose: Currently, there is a claim for earlier interventions for families in order to prevent child maltreatment. Here, a screening instrument to assess risk indicators for child abuse and neglect already in the context of maternity clinics is introduced. The present study is the first report on the psychometric properties of this instrument, the “short questionnaire for risk indices around birth” (RIAB). Material and Methods: Data were collected in the context of three different studies conducted at Ulm University Hospital. To examine interrater reliability eight case vignettes were rated by n = 90 study participants (50 students and 40 experts working at a maternity clinic). Criterion validity was examined in two studies applying the German version of the child abuse potential inventory CAPI (n = 96 families at risk and n = 160 additional families). Results: Both laymen and experts were able to understand and use the screening instrument correctly, leading to a high agreement with the sample solutions given. A high concordance was found between parentsʼ and expertsʼ ratings: In case of no reported risk factors applying the screening instrument RIAB, parents themselves reported significantly less stressors and burdens, compared to those parents with an indication for a thorough examination as pointed out in the RIAB. Conclusion: In the context of maternity clinics the RIAB is a useful, broadly applicable instrument, screening for existing risk factors at the earliest and thus allowing for the initiation of specific interventions when needed.
Keywords: early prevention and intervention; obstetrics; child protection; prevention; screening